Cultivation of Nutrientdense and Climateresilient Traditional Vegetable Crops in Urban Community Gardens - Monville Oro, Emilita; Shreinemachers, Pepijn (CGIAR Initiative on Resilient Cities, 2024)
The Demonstration Gardens for Nutrient Dense and Climate-Resilient Traditional Vegetable Crops in Quezon City is part of the CGIAR Resilient Cities initiative. Supported by the World Vegetable Center (WVC) and implemented by the International Institute of Rural Reconstruction (IIRR), in collaboration with Quezon City's Local Government Units’ Joy of Urban Farming Program and the Institute of Plant Breeding at the University of the Philippines Los Baños (IPB-UPLB), the project aims to trial a variety of nutrient rich traditional vegetable crops in an urban setting These crops will diversify the existing selection in Joy of urban farm community gardens, providing a demonstration and learning space for schools, institutions, and other organizations to explore neglected and underutilized crops with potential to improve garden resilience and enhance the nutrition of vulnerable urban families.